The combined action of monocytic myeloid‐derived suppressor cells and mucosal‐associated invariant T cells promotes the progression of cervical cancer. Issue 6 (4th December 2020) - Lu, Zhimin; Zhu, Mengting; Marley, Jordan Lee; Bi, Kaihuan; Wang, Kangxia; Zhai, Muxin; Hu, Hui; Guo, Peipei; Li, Caihua; Xu, Yuping; Chen, Ya; Zhou, Ping; et al.
Abstract: One of the most common promoters of the initiation and growth of the tumor is an immune disturbance. Numerous immune cells and inflammatory factors play a role in the tumor‐immune microenvironment. However, few studies have investigated the correlation between these immunological events and clinical consequences in cervical cancer. We measured the levels of numerous inflammatory mediators and frequencies of regulatory T cells (Tregs), myeloid‐derived suppressor cells (MDSCs) and mucosal‐associated invariant T (MAIT) cells in peripheral blood (PB) of cervical cancer patients. Cervical cancer patients showed elevated production of interleukin (IL)‐18 and plasma C‐C chemokine ligand (CCL) 3/5. Meanwhile, an accumulation of C‐C chemokine receptor 5 (CCR5) monocytic (Mo)‐MDSCs and Tregs was observed. The cervical cancer group displayed increased frequencies of CD8 +, CD4 + and highly activated CD38 + CD8 + MAIT cells, and reduction of double‐negative (DN) and PD1(CD279 + ) DN MAIT cells. Importantly, it was demonstrated that MAIT cells were positively related to Mo‐MDSCs. Furthermore, an elevated concentration of PD1(CD279 + ) DN MAIT cells was significantly related to increased progression‐free survival of patients with cervical cancer. In conclusion, our study suggests that the combined action of Mo‐MDSCs and MAIT cells might be associated with the progression of cervical cancer, and the frequency of DN MAIT cells in the peripheral blood mononuclear cells was associated with the survival benefit of patients. What's new?: There is increasing evidence showing the importance of a dysfunctional host immune response in cervical cancer progression. The underlying mechanisms and their clinical relevance remain to be clarified, however. Here, the authors reveal a complex association between chronic inflammation, myeloid‐derived suppressor cells (MDSCs), mucosal associated invariant T (MAIT) cells, and disease progression in cervical cancer and cervical intraepithelial neoplasia. Patients showed an accumulation of CCL2/3/5, IL‐18, monocytic MDSCs, and MAIT cells. Moreover, the combined action of monocytic MDSCs and MAIT cells was related to progression of cervical cancer, while high levels of CD4‐CD8‐ MAIT cells might have a protective role.